Amputation risk after the revascularization procedures in sarcoma resections - Luiz Eduardo Moreira Teixeira; Thiago Marques Leão; Daniel Barbosa Regazzi; Cláudio Beling Gonçalves Soares (Revista Brasileira de Ortopedia)
ABSTRACT OBJECTIVE: The objective of this study is to evaluate the efficacy of vascular reconstructive surgery after resection of bone and soft tissue tumors in extremities and the risk of progression to amputation. METHODS: This is a retrospective, observational data collection from medical records of patients who underwent resection of bone and soft tissue tumors in the period of 2002-2015. Thirteen patients met the inclusion criteria, which evaluated the correlations between certain factors (gender, tumor type, location, reconstruction, revascularization and patency, infection) with amputation in the postoperative period. RESULTS: In this study, of the 13 patients undergoing reconstruction, five (38.46%) evolved to amputation. All patients who progressed to amputation had the following in common: presence of bone sarcoma (p = 0.005), having undergone reconstruction with an orthopedic prosthesis (p = 0.005), lack of vascular patency in the revascularization site in the postoperative period (p = 0.032), and surgical site infection (p = 0.001). None of the patients with soft tissue sarcoma underwent amputation, and the only patient with bone sarcoma who did not undergo amputation had no infection and maintained vascular patency of the graft. CONCLUSION: The occurrence of infection appears to be one of the main risk factors for failure of revascularization, especially in cases of bone sarcoma in which vascular reconstruction is performed with placement of a non-conventional joint prosthesis.